PERMASALAHAN-PERMASALAHAN PENGELOLAAN PENDIDIKAN DASAR - Poni Egistin, Dwi; Pratasya, Meynita; Harnida, Sepni; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article aims to describe the problems of primary school management. This research uses literature study as its main research method, utilizing data collection from various reading sources such as journals, books and articles. The literature study serves as a valuable means of obtaining in-depth information for this research endeavor. The education system in Indonesia is nationally standardized in management. In general, education management standards are made to homogenize the quality of management in schools. But specifically, it is necessary to analyze each point in order to develop the quality of education services in the schools that implement it. The analysis must be able to support the development of educational institutions to become more professional and adapt to the needs of society.